Pengaruh Kepemimpinan, Motivasi Kerja, Kepuasan Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Pt Klasse Mitra Internasional - Syah, Andrian; Siahaan , Leonard (Blantika: Multidisciplinary Journal, 2025)
This study aims to analyze the influence of leadership, work motivation, job satisfaction, and work environment on employee performance at PT Klasse Mitra Internasional. Using a quantitative method and survey approach, data were collected from 60 permanent employees through a census technique. The questionnaire used was tested for validity and reliability, with Cronbach’s Alpha values ranging from 0.831 to 0.948. Descriptive statistics showed that all variables were perceived in the "High" to "Very High" category. Classical assumption tests confirmed that the regression model met the requirements of normality, no multicollinearity, and homoscedasticity. Simultaneous testing revealed that leadership, work motivation, job satisfaction, and work environment significantly influence employee performance (Sig. 0.020 < 0.05). However, partial testing showed that only leadership had a positive and significant effect (B = 0.287; Sig. 0.022), while work motivation had a negative and significant effect (B = -0.271; Sig. 0.009), indicating a mismatch between motivational systems and employee expectations. Job satisfaction and work environment had no significant partial effect. The coefficient of determination (R²) was 0.188, indicating that 18.8% of the variance in employee performance could be explained by the four variables, while the remaining 81.2% was influenced by other factors outside the model. Based on these findings, the company is advised to optimize leadership quality and re-evaluate the work motivation system, while future research should consider exploring other variables and adopting a qualitative approach for deeper insight into employee performance dynamics.